2016
DOI: 10.1175/bams-d-14-00239.1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Thunderstorms That Produce Terrestrial Gamma Ray Flashes

Abstract: Ground-based lightning detection systems geolocated 877 terrestrial gamma ray flashes (TGFs) from a sample of 2,279 TGFs detected with the Fermi Gamma Ray Burst Monitor (GBM). From these accurate geolocations, 24 TGFs are found within the Next Generation Weather Radar (NEXRAD) operational range in the Gulf of Mexico, the Caribbean, and the Pacific near Guam. NEXRAD-enhanced echo-top (EET) data show that these 24 TGFs are consistently adjacent to high-altitude regions of the storms. The high EET values suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
53
2
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 65 publications
16
53
2
1
Order By: Relevance
“…In some other cases, no sounding data were available. The estimated cloud top heights provided in this study were all found to be ≥9.5 km, similar to values reported previously in Chronis et al []. Some of the cloud top heights are suggestive of some TGFs being produced from overshooting cloud tops, with altitudes of ≥17 km.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In some other cases, no sounding data were available. The estimated cloud top heights provided in this study were all found to be ≥9.5 km, similar to values reported previously in Chronis et al []. Some of the cloud top heights are suggestive of some TGFs being produced from overshooting cloud tops, with altitudes of ≥17 km.…”
Section: Resultssupporting
confidence: 89%
“…This might be expected as the IC+ association must have a peak current comparable or greater than CG lightning in order to be detected by the WWLLN. The finding that even such weak storms are capable of producing TGFs is in keeping with the conclusions drawn from Chronis et al [], although further investigation into such storms is required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meteorological images acquired by geostationary satellites (Meteosat‐10, Himawari‐7, and GOES 13/15) included in the AGILE meteoretrieving pipeline show the presence of convective systems in the region of interest, frequently lasting several hours in order to produce more TGFs detected at successive passages. These data show that the underlying thunderstorms producing multiple TGFs exhibit very different extensions and structures, quite consistent with the results found by Splitt et al [] and Chronis et al [], suggesting that there are no privileged types of thunderstorm for TGF production.…”
Section: Discussionsupporting
confidence: 91%
“…For one of the TGFs in the sample, we can verify our results by comparing the estimated altitude for the preferred model with an altitude that is determined independently using radar measurements [ Chronis et al , ]. For TGF130930128, we find that the estimated cloud top height is in agreement with the source altitude measurements from the spectral analysis.…”
Section: Discussionsupporting
confidence: 69%